An Inscription from Myra Honouring Platon, the Priest of the Lycian League, and his Family - (:unkn) unknown (SUNA & INAN KIRAC RESEARCH INST MEDITERRANEAN CIVILIZATIONS, 2016)
In the 2011 campaign of excavations at Myra, a new honorary monument was uncovered just in front of the rear wall of the theatre's stage building. The monument is comprised of four inscribed blocks registered as no. 72 by the author and was erected in honour of Platon the priest, his father Polyperchon, and his son Platon II after their deaths. The inscription can be dated to the Late Hellenistic-Early Roman periods based on the letter-forms. The honorary inscriptions presented in this article introduce a wealthy family of Myra from the Late Hellenistic-Early Roman periods. It is possible to track this family for four generations, and they seem to have undertaken certain magistracies and benefactions only within Myra. However, Platon I was the eponymous priest of the Lycian League, which shows that the family had ascended the ranks among the dignitaries of the League. It is not known at the present time whether family members undertook other services at the League level afterwards. It is possible that ongoing excavations will uncover other inscriptions that will cast light onto the subsequent generations of this family.